Anti-Doping policies: The Olympics and selected professional sports - Halchin, L. E. (Hot topics in sports and athletics, 2008)
The use of performance-enhancing substances by athletes has a long history, predating the ancient Greek Olympiads. Concern about this practice was manifested in the 20th century by, in the case of the Olympics, the creation of anti-doping organizations, and the adoption of anti-doping policies by these organizations and professional sports leagues in the United States. Leading the way was the International Olympic Committee (IOC), which implemented testing in 1968 at the Olympic Games in Grenoble, France, and Mexico City, Mexico. The National Basketball Association (NBA) and the National Football League (NFL) followed suit in the 1980s. Major League Baseball implemented an anti-drug policy in 2003.